Patients' priorities for treatment decision making during periods of incapacity: quantitative survey. Issue 5 (October 2015) - Rid, Annette; Wesley, Robert; Pavlick, Mark; Maynard, Sharon; Roth, Katalin; Wendler, David
Abstract: Objective: Clinical practice aims to respect patient autonomy by basing treatment decisions for incapacitated patients on their own preferences. Yet many patients do not complete an advance directive, and those who do frequently just designate a family member to make decisions for them. This finding raises the concern that clinical practice may be based on a mistaken understanding of patient priorities. The present study aimed to collect systematic data on how patients prioritize the goals of treatment decision making. Method: We employed a self-administered, quantitative survey of patients in a tertiary care center. Results: Some 80% or more of the 1169 respondents (response rate = 59.8%) ranked six of eight listed goals for treatment decision making as important. When asked which goal was most important, 38.8% identified obtaining desired or avoiding unwanted treatments, 20.0% identified minimizing stress or financial burden on their family, and 14.6% identified having their family help to make treatment decisions. No single goal was designated as most important by 25.0% of participants. Significance of Results: Patients endorsed three primary goals with respect to decision making during periods of incapacity: being treated consistent with their own preferences; minimizing the burden on their family; and involving their family in the decision-making process. However, no single goal was prioritized by a clear majority of patients. These findings suggest that advance care planning should not be limited to documenting patients' treatment preferences. Clinicians should also discuss and document patients' priorities for how decisions are to be made. Moreover, future research should evaluate ways to modify current practice to promote all three of patients primary goals for treatment decision making.